A rare primary thyroid mixed germ cell tumour: a case report - R., W. Suriza W. A.; I., Junaidi A.; M., Helmi N.; H., Imi Sairi A. (International Surgery Journal, 2022)
Germ cell tumours mostly occur in the gonads. Extragonadal site is rare and mainly located in the mediastinum, retroperitoneum and pineal gland. Germ cell tumour that occurs in the thyroid gland is extremely rare. We present our first description of a patient with a mixed germ cell tumour located primarily in the thyroid gland. A 35 years old gentleman presented with two months history of thyroid swelling associated with compressive symptoms. His neck ultrasound showed multinodular goiter with suspicious nodule (TR4) and FNAC revealed highly suggestive of a malignant lesion. Subsequently, the thyroid mass progressively enlarged in size causing acute upper airway obstruction that made him collapsed at Emergency Department. Core biopsy of TR4 thyroid nodule suggestive of malignant lesion which could be mixed germ cell tumour or poorly differentiated carcinoma. Abnormal laboratory tests showed a high concentration of LDH, Alpha fetoprotein and beta-HCG. He underwent emergency total thyroidectomy, debulking and tracheostomy. Histopathology reported the mass composed of mixed non-seminomatous germ cell tumour with area of necrosis (30%), primarily immature elements (80%), yolk sac tumour (15%) and embryonal carcinoma (5%). He was scheduled for chemotherapy post operatively however he succumbed to the illness due to advanced tumour and sepsis.